Peer-to-peer mentoring for individuals with early inflammatory arthritis: feasibility pilot. Issue 3 (1st March 2013) - Sandhu, Sharron; Veinot, Paula; Embuldeniya, Gayathri; Brooks, Sydney; Sale, Joanna; Huang, Sicong; Zhao, Alex; Richards, Dawn; Bell, Mary J
Abstract : Objectives: To examine the feasibility and potential benefits of early peer support to improve the health and quality of life of individuals with early inflammatory arthritis (EIA). Design: Feasibility study using the 2008 Medical Research Council framework as a theoretical basis. A literature review, environmental scan, and interviews with patients, families and healthcare providers guided the development of peer mentor training sessions and a peer-to-peer mentoring programme. Peer mentors were trained and paired with a mentee to receive (face-to-face or telephone) support over 12 weeks. Setting: Two academic teaching hospitals in Toronto, Ontario, Canada. Participants: Nine pairs consisting of one peer mentor and one mentee were matched based on factors such as age and work status. Primary outcome measure: Mentee outcomes of disease modifying antirheumatic drugs (DMARDs)/biological treatment use, self-efficacy, self-management, health-related quality of life, anxiety, coping efficacy, social support and disease activity were measured using validated tools. Descriptive statistics and effect sizes were calculated to determine clinically important (>0.3) changes. Peer mentor self-efficacy was assessed using a self-efficacy scale. Interviews conducted with participants examined acceptability and feasibility of procedures and outcome measures, as well as perspectives on the value of peer support for individuals with EIA. Themes were identified through constant comparison. Results: Mentees experienced improvements in the overall arthritis impact on life, coping efficacy and social support (effect size >0.3). Mentees also perceived emotional, informational, appraisal and instrumental support. Mentors also reported benefits and learnt from mentees' fortitude and self-management skills. The training was well received by mentors. Their self-efficacy increased significantly after training completion. Participants' experience of peer support was informed by the unique relationship with their peer. All participants were unequivocal about the need for peer support for individuals with EIA. Conclusions: The intervention was well received. Training, peer support programme and outcome measures were demonstrated to be feasible with modifications. Early peer support may augment current rheumatological care. Trial registration number: NCT01054963, NCT01054131 .